1993
DOI: 10.1002/jmri.1880030515
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hepatocyte‐specific paramagnetic contrast media for MR imaging of hepatitis

Abstract: The hepatocyte-specific paramagnetic magnetic resonance (MR) contrast agents manganese-DPDP [N,N'-dipyridoxylethylenediamine-N,N'-diacetate 5,5'bis-(phosphate)] and gadobenate dimeglumine were used for diagnosing chemically induced hepatitis in rats. Ex vivo liver tissue relaxation times and in vivo MR image signal-to-noise ratios were compared before and after contrast agent administration. Ex vivo relaxometry and in vivo MR imaging showed that Mn-DPDP enhanced normal and diseased livers to the same degree at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The efficacy results for the delayed (4 and 24 hours post injection) imaging trial (21) and the safety results for both trials (22) are being reported separately. Already reported elsewhere are the efficacy results from nonclinical studies (5, 23–44) and phases I (6, 45–47) and II (8–18, 48–57) and European phase III 25, 56, 58–65 clinical studies.…”
mentioning
confidence: 99%
“…The efficacy results for the delayed (4 and 24 hours post injection) imaging trial (21) and the safety results for both trials (22) are being reported separately. Already reported elsewhere are the efficacy results from nonclinical studies (5, 23–44) and phases I (6, 45–47) and II (8–18, 48–57) and European phase III 25, 56, 58–65 clinical studies.…”
mentioning
confidence: 99%
“…12,13 It has been documented that injured livers show sustained liver enhancement with MnDPDP. 30,31 Previous expectations that a contrast agent could be used to detect cancer (by enhancing liver) [9][10][11]18 and distinguish normal liver from hepatitis (by not enhancing liver) 12,13 are somewhat contradictory. This study conˆrms that MnDPDP and SPIO-AG maintain cancer detection despite the presence of hepatitis.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations for the preservation of liver-speciˆc enhancement in the presence of hepatocellular injury are as follows: First, the biodistribution of the drug might not be changed at all, because the uptake mechanisms are not aŠected by the hepatic injury; second, the normal uptake mechanisms are impaired in hepatic injury, but the liver might have an alternative mechanism for drug uptake; third, while the uptake might be reduced, relaxivity might be increased in the altered intracellular environment;ˆnally, it should be augured that the echo time used in T1-weighted SE 310 W 15 images may be too long to diŠerentiate between normal and injured livers. 30 Theˆrst explanation might account for the enhancement with MnDPDP in hepatitis. It is not fully understood whether the uptake mechanism of MnDPDP is energy-dependent and whether it is the same as that of pyridoxal 5?…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that radionuclide scanning could reflect liver function to some extent, but it is still difficult to quantitate liver function with imaging tests [5,6]. The paramagnetic hepatobiliary complexes have been tested in the evaluation of acute liver damage [7]. These studies were based on the targeting strategy as well as radionuclide scanning, with better spatial resolution of MR imaging.…”
Section: Discussionmentioning
confidence: 99%